PEMIKIRAN KI HAJAR DEWANTARA TENTANG PENDIDIKAN INDONESIA - Aulia Novianty Ardini; Dewi Khumairoh Al Ulfah; Debi Setiawati (Puteri Hijau : Jurnal Pendidikan Sejarah, 2023)
The development of education in Indonesia cannot be separated from the role of Ki Hajar Dewantara, who is the father of education in Indonesia. At the present time, his thinking is based on the independent learning curriculum concept. Therefore, through this article, the author aims to describe the Thoughts of Ki Hajar Dewantara on Education in Indonesia. This paper is a literature review using a historical approach. The primary data sources that will be used include works written by Ki Hajar Dewantara that have been written by other people. In the process of analyzing the data that has been collected, the author uses content analysis. The results of his research are: 1) Ki Hajar Dewantara’s conception of education includes the concept of Tut Wuri Handayani; 2) Ki Hajar Dewantara’s thoughts on education in Indonesia 3) Renewal of Ki Hajar Dewantara’s thoughts on education in Indonesia Education is one of the most important things to do, both in Indonesia and abroad. The purpose of education itself is to make a person have a good personality and broad insight. In general, education refers to the learning, knowledge, and skills possessed by a person. However, some experts have their own education, including Ki Hajar Dewantara. Thanks to his work in the field of education, Ki Hajar Dewantara is called the father of education in Indonesia. First, Ing Ngarso Sung Tulodo must set an example in front. From this, we can conclude that the behavior of students can be influenced by their teachers; therefore, teachers must always reflect on whether they really set a good example by giving knowledge to their students or only provide knowledge without teaching good morals as well. Second, Ing Madyo Mangun Karso (must give an idea in the middle). This motto prevents teachers from considering students as lower beings than their teachers. Under this motto, we can know that as teachers, we must be friends who can hug their students. Third, Tut Wuri Handayani (behind the back must be able to provide encouragement) means that teachers must always provide positive encouragement to all students. Therefore, teachers are expected to be able to motivate their students to realize their dreams. The teacher’s task is to help students develop, find, and search for the talents that exist in them.